Exploring the experiences of intimate partner violence against women in Seshego Zone1, Limpopo Province - Seanego, Chuene Lonia (My University, 2022)
This study intended to explore Intimate Partner Violence (IPV) against women in the Seshego Zone 1 area, which is situated in the Polokwane Municipality of the Limpopo Province. The different types of IPV against women, the prevalence of IPV against women, the causes of IPV against women, the reasons for not reporting IPV against women, as well as the available measures taken to combat this scourge guided this study. This study followed a qualitative research approach, where 17 participants were purposively selected, and this was coupled with snowball sampling. Face-to-face in depth semi-structured interviews were utilised to collect data to explore the IPV against women. The collected data was analysed by means of Inductive Thematic Content Analysis (TCA). The responses were audio recorded and written down to add value to the study findings. Themes and sub-themes were solicited from the participants’ verbatim expressions. This study established that the rate of IPV against women cases are high and has been increasing during the period of study because the victims are not taken seriously when reporting. It was also confirmed that jealousy and poverty are the major causes of IPV against women in the area. The victims often fail to seek support and do not report to the police when the violence takes place. It was also evident that most people seem to lack exposure on the issues of IPV against women and the lack of economic and employment opportunities in the area hinder women empowerment against violence and this should be urgently addressed. This study recommends that the local police should learn to take the cases of IPV against women seriously so that the rate of violence can decrease and the victims of IPV against women should be able to identify the signs and prevalence of this practice to effectively prevent it. Moreover, the victims should be encouraged to report cases to the police, and they must demand progress reports on the cases. As a result, the women continue to suffer due to violence in the study area. Moreover, this study suggests that there must be local support groups for women who experience violence in the community to help in detailing the consequences of IPV against women. This should be aided by various awareness campaigns to alert men that IPV against women is a criminal offence, and it is punishable. The government should also support women to start small businesses to reduce full dependence on their partners, thereby reducing the risks of IPV.
Thesis (M.A. (Criminology and Criminal Justice)) -- University of Limpopo, 2022
Keywords: Exploration; Experience; Violence; Intimate partner violence against women; Women; Intimate partner violence; Dating violence; Women -- Abuse of; Women -- Abuse of -- South Africa -- Limpopo